2012
DOI: 10.1097/mib.0b013e318280ea9e
|View full text |Cite
|
Sign up to set email alerts
|

HMPL-004 (Andrographis paniculata extract) Prevents Development of Murine Colitis by Inhibiting T-cell Proliferation and TH1/TH17 Responses

Abstract: Background-Extracts of the plant Andrographis paniculata have been used to treat inflammatory diseases in Asian countries. A recent double blind, placebo controlled, trial of HMPL-004 (A. paniculata extract) has demonstrated its safety and effectiveness for induction of clinical response, remission, and mucosal healing in patients with mild to moderate UC. We aimed to determine if HMPL-004 could prevent the development of T cell dependent murine colitis and to define its in vivo mechanism(s) of action

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…This trial followed a double‐blind RCT published by Tang et al in 2011, in which HMPL‐004 had shown an efficacy not significantly different from that of mesalamine, at week 8, in patients with mild‐to‐moderate UC (Tang et al , ). In a T‐cell‐driven model of murine intestinal inflammation, HMPL‐004 was able to prevent the development of colitis by inhibiting the proliferation of CD4+ T lymphocytes and their differentiation into Th1/Th17 cells (Michelsen et al , ). These anti‐inflammatory effects of Andrographis paniculata were mimicked by its main component, andrographolide, in mice with TNBS‐induced colitis (Liu et al , ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…This trial followed a double‐blind RCT published by Tang et al in 2011, in which HMPL‐004 had shown an efficacy not significantly different from that of mesalamine, at week 8, in patients with mild‐to‐moderate UC (Tang et al , ). In a T‐cell‐driven model of murine intestinal inflammation, HMPL‐004 was able to prevent the development of colitis by inhibiting the proliferation of CD4+ T lymphocytes and their differentiation into Th1/Th17 cells (Michelsen et al , ). These anti‐inflammatory effects of Andrographis paniculata were mimicked by its main component, andrographolide, in mice with TNBS‐induced colitis (Liu et al , ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Recent studies have shown that biological agents targeting more than one cytokine have the potential to increase the therapeutic success [5,66,67]. In this study, we used siRNA directed against IP-10 and KC in addition to siRNA directed against TNF-α to enhance the therapeutic effect of only one regulated gene.…”
Section: Discussionmentioning
confidence: 99%
“…Its extract (HMPL-004) has potent anti-inflammatory properties by inhibiting NF-κB activity, and its use is being explored in various medical conditions. In experimental colitis, HMPL-004 has been shown to affect T cell proliferation and differentiation and Th1/Th17 responses 100. Its clinical use has been already explored in phase II trials in UC.…”
Section: Innovative Ways For Drug Discoverymentioning
confidence: 99%